Singlet and triplet states dissociation of doubly charged HDO, H2O and D2O as a function of internal energy. (July 2015) - Martin, S; Chen, L; Brédy, R; Bernard, J; Cassimi, A
Synopsis: The fragmentation of HDO 2+, H 2 O 2+ and D 2 O 2+ is reported as a function of the excitation energy. The doubly charged ions were prepared selectively to triplet or singlet excited states in collisions with F + and H + at 3 keV, respectively. For HDO 2+ the isotopic ratio, ratio of probabilities for the two dissociation channels OD + — H + over OH + — D +, was estimated to be 4.5 ± 0.8 using H + and 3.8 ± 0.8 using F + projectiles. Results are compared with recent calculations.